Modelling clay–fluid interactions in montmorillonite clays. Issue 5 (27th January 2016) - Katti, Dinesh R; Patwary, Zillur R; Katti, Kalpana S
Abstract : This study shows that flow properties and degree of swelling of sodium (Na) montmorillonite (MMT) clay depend significantly on the polarity of solvents. The behaviour of sodium MMT clays intercalated with fluids with a range of dielectric constants, from highly polar formamide (110) to very low-polarity toluene (2·4), using molecular dynamics simulations. These fluids are commonly found in landfill leachates and are identified as highly toxic by the Environmental Protection Agency. Typically, the higher the polarity of fluids, the lower is their mobility, resulting in retention inside clay interlayer, causing greater swelling and swelling pressure. From interaction energy calculations, it is observed that clay–clay electrostatic interactions contribute only 1–6% of the total clay–fluid or sodium ion–fluid interactions. This study suggests that hydration of clay surfaces and counter-ions are the dominating factors of clay swelling, rather than the interaction between negatively charged clay sheets. Also, at lower fluid concentrations, interlayer fluids show organised orientation. This study also provides insight into molecular mechanisms that lead to the macro-scale behaviour of swelling clays. Significant variation in flow properties and swelling of clays with fluids of different polarities are important considerations for landfill liner designs, as well as other geotechnical and geoenvironmental applications.